Study of Mechanical Characteristics of Silicon Carbide Reinforced Zn-Mg Based Metal-Ceramic Composite - Rai A.; Rai P.; Kumar A.; Chaturvedi R.K.; Singh V.K. (My University, 2025)
When hard particles are reinforced to a metal matrix, the mechanical and physical characteristics of the base matrix improve dramatically. The article investigates the mechanical characteristics and strengthening mechanism of the zinc-based matrix by reinforcement of silicon carbide (SiC) particles. In the present work, the Zn-Mg-SiC composite was made by powder processing approach with varying amounts of SiC viz. 0% SiC, 2% SiC, 4% SiC, 6% and 8% SiC. Mechanical properties increased with increase in SiC content up top 6% and then decreased due to the dominant agglomeration of particles. It was found that the composite reinforced with 6% SiC content has optimized hardness, compressive strength, flexural strength, and stiffness. The crystallite size was found to have a remarkable effect on the mechanical characteristics of the composites. The composite with 6% SiC content has a minimum crystallite size having a value of 30.25 nm. The dislocation density results depicted that the composite with 6% SiC has a maximum dislocation density of 3.6 nm−2. The enhancement in mechanical characteristics is attributed to the elevation in dislocation density of the composite and the reduction in crystallite size and grain size. © 2023, The Author(s), under exclusive licence to Springer Nature B.V.